P1448FACTORS ASSOCIATED WITH INCREASED MORTALITY AFTER DIALYSIS INITIATION. RESULTS OF THE PERIDIALYSIS STUDY. (6th June 2020) - Heaf, James G; Heiro, Maija; Petersons, Aivars; Vernere, Baiba; Povlsen, Johan Vestergaard; Sørensen, Anette Bagger; Clyne, Naomi; Bumblyte, Inge; Zilinskiene, Alanta; Randers, Else; Løkkegaard, Niels; Ots-Rosenberg, Mai; et al.
Abstract: Background and Aims: Home dialysis with peritoneal dialysis (PD) or home hemodialysis (HD) has medical and socioeconomic benefits but home dialysis is generally underutilized. While many factors determine choice of initial dialysis modality, starting patients on home dialysis requires timely planning, educational activities and an active program to promote home dialysis. Here we investigated factors including patient suitability, pre-dialysis preparations and institutional factors determining choice of dialysis modality among patients initiating dialysis. Method: Choice of dialysis modality was investigated in 1588 consecutive patients (age 63.8 ±15.3 years. 35.8% female; diabetic nephropathy 24.4%) participating in the Peridialysis study, a multinational multi-centre prospective study of causes and timing of planned and unplanned dialysis initiation (DI) over a 3-year period in 15 Nordic and Baltic nephrology departments. All dialysis modalities were available and free of charge to patients. All centres offered pre-dialysis education programs to patients with timely referral. Clinical and biochemical data during the pre-dialytic period, centre data, and reasons for DI and choice of dialysis modality were registered. Results: 516 (32.4%) patients were not offered home dialysis because they were judged to be unsuitable (384 ; 24%): PD was contraindicated in 338 (21.2%) patients - for physical (142; 8.9%), mental (80, 5.0%) or abdominal (116; 7.3%) reasons and HD was contraindicated in 46 (2.9%) patients. In addition, 106 (6.7%) were not offered home dialysis for various reasons; and deaths before modality choice occurred in 26 (1.6%) patients. Factors associated with unsuitability were high age, comorbidity, late referral (risk ratio, RR, 1.9), inflammation (C-reactive protein >50 mg/L (RR 2.6) and rapid loss of renal function (RR 2.0). Patients who were not assessed for home dialysis comprised mainly patients with late referral (RR 5.8) and/or unplanned DI (RR 9.6). Of the remaining 1072 (67.6%) patients, who had a free choice of modality, 700 (65.3%) chose home dialysis, either PD (661 ; 61.7%) or home HD ( 39: 3.6%) while 372 (34.7%) patients chose centre HD. Factors associated with choice of centre dialysis were late referral (RR 1.8), suboptimal DI (RR 2.0), symptomatic uraemia (RR 1.6) and p-urea >30 mM (2.6). Somatic differences between patients choosing home dialysis and centre dialysis were minor. Independent institutional factors reducing information about home dialysis were treatment at a university hospital (RR 4.3) and absence of an active preference for home dialysis, "home dialysis first" policy (RR 3.0). Conclusion: The results of the Peridialysis study indicate that the incidence of home dialysis could be increased by a "home dialysis first" department policy and by efforts to reduce the incidence of late referrals and unplanned DI. Acutely ill patients and patients with unplanned DI may be candidates for home dialysis if assessment of home dialysis suitability and dialysis educational program are performed after their clinical condition has improved. Given a free choice, most patients (65%) choose home dialysis.